2012
DOI: 10.1371/journal.pone.0051193
|View full text |Cite
|
Sign up to set email alerts
|

Inter-Specific Competition, but Not Different Soil Microbial Communities, Affects N Chemical Forms Uptake by Competing Graminoids of Upland Grasslands

Abstract: Evidence that plants differ in their ability to take up both organic (ON) and inorganic (IN) forms of nitrogen (N) has increased ecologists’ interest on resource-based plant competition. However, whether plant uptake of IN and ON responds to differences in soil microbial community composition and/or functioning has not yet been explored, despite soil microbes playing a key role in N cycling. Here, we report results from a competition experiment testing the hypothesis that soil microbial communities differing i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
(75 reference statements)
1
3
0
Order By: Relevance
“…Furthermore, while the warming treatment in this study only increased air temperature by 0.35 °C, we found no associations between Eriophorum growth and air temperature (range across all plots within the growing season: 13 °C). This suggests that microclimate is not a major factor regulating Eriophorum growth in this ecosystem, and is in agreement with previous studies examining Eriophorum growth, which have found it to be primarily nutrient limited (Kool and Heijmans 2009;Medina-Roldán and Bardgett 2012). The bryophyte plant functional type at our study site comprises 9 % P. schreberi (Ward et al, unpublished data), a feather moss that fixes atmospheric nitrogen (N) through symbiotic associations with cyanobacteria (DeLuca et al 2002).…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, while the warming treatment in this study only increased air temperature by 0.35 °C, we found no associations between Eriophorum growth and air temperature (range across all plots within the growing season: 13 °C). This suggests that microclimate is not a major factor regulating Eriophorum growth in this ecosystem, and is in agreement with previous studies examining Eriophorum growth, which have found it to be primarily nutrient limited (Kool and Heijmans 2009;Medina-Roldán and Bardgett 2012). The bryophyte plant functional type at our study site comprises 9 % P. schreberi (Ward et al, unpublished data), a feather moss that fixes atmospheric nitrogen (N) through symbiotic associations with cyanobacteria (DeLuca et al 2002).…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, in upland systems the intervening dry periods between events can lower microbial mineralization rates (Borken & Matzner, ; Fierer & Schimel, ). Our results suggest that N‐uptake in monocot wetlands species is not affected by precipitation frequency (Table ), perhaps because graminoids are also able to utilize soil organic‐N (Gao, Mo, Xu, Zhang, & Yu, ; Medina‐Roldan & Bardgett, ). In contrast, N‐content and C:N ratios were influenced by precipitation frequency and magnitude for two eudicots, E. perfoliatum and M. ringens (Table ).…”
Section: Discussionmentioning
confidence: 72%
“…Thus, it is important to develop a predictive understanding of the factors controlling the amount of available N within an ecosystem, which includes both the inorganic (nitrate and ammonium) and organic forms that can be assimilated by plants and microorganisms [3][4]. The amount of available N in an ecosystem is controlled by the cumulative effects of microbially-driven N inputs through N-fixation, by the mineralization of N from organic matter, and by N-losses through leaching and gas emissions [5]–[6].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the emergence of new paradigms for soil N cycling that emphasize the importance of both organic and inorganic N forms [3][4], [18], and the growing literature on the topic, we lack an integrated understanding of the most important determinants of N availability. This is particularly true for N-poor ecosystems such as drylands (arid, semiarid and dry-subhumid ecosystems; [22][24]).…”
Section: Introductionmentioning
confidence: 99%